Economic Evaluation of Islamic Banking in Pakistan - Shaikh, Salman Ahmed (Journal of King Abdulaziz University: Islamic Economics, 2023)
The term Islamic in Islamic banking naturally raises the question of what this word adds to the concept and practice of banking? The early literature on Islamic economics raised the bar of expectations and envisioned Islamic banking as distinct from conventional banking by avoiding interest in letters and spirit. Interest-based banking was thought to suffer from exclusion, inequality, injustice, misallocation of capital resources and concentration of capital. It was thought that Islamic banking, while avoiding interest, would be more inclusive, equitable, and fair and would result in a broad allocation of resources without the exclusionary criterion of a fixed cost of capital. It was also thought that this new banking system would reduce income and wealth inequalities and control the concentration of wealth. Today, after two decades of Islamic banking in Pakistan, it is pertinent to assess the progress and performance of these ideals. This study evaluates Islamic banking in terms of inclusiveness, competitiveness, and equity. The economic assessment shows that Islamic banks have secured financial inclusion for those who wish to avoid ribā. However, concerted efforts are needed to improve competitiveness and distinction regarding distributional impact of Islamic financial products.